Ayurvedic Management of Shushkakshipaka w.s.r. To Dry Eye Syndrome - A Single Case Study - Devi, Poonam; Vinaik, Ashu; Tanwar, Manoj (International Research Journal of Ayurveda & Yoga, 2024)
Eyes are one of the most powerful tools that anyone can have; hence, all efforts should be made to protect the eyes. In today’s era, people depend more on machines like computers in all sectors of life. These cause some heat and radiation which certainly causes ill effects on the eyes. Tear (Ashru) secretion is an integral component of the ocular surface physiology; when compromised (quantitatively or qualitatively) leads to shushkakshipaka (dry eye syndrome) with various ocular discomfort symptoms and ultimately the patient may land in corneal blindness. Local, systemic, and environmental factors majorly affect its pathogenesis. Vata and Pitta/Rakta vitiation as per Ayurvedic viewpoint are the major contributing pathological factors in its manifestation. A 28-year-old female patient approached Shalakya OPD of SKGAC and H, Kurukshetra, complaining of irritation, foreign body sensation, eye fatigue, and pain in the periorbital region along with a feeling of dryness for 1 year. The patient had slight symptomatic relief but when medications were discontinued the condition used to reoccur, so she turned to Ayurvedic treatment for relief. In Ayurveda classics, specific treatment has been mentioned for Shushkakshipaka such as Snehana ( in-take of Ghee), Tarpana ( retention of ghee over eyes), Nasya ( Nasal medication), and Pariseka ( ocular irrigation). A patient of shushkakshipaka was treated with such treatment protocol, is presented as a case study in this article. Contrary to the available modern medical treatment Ayurveda propounds a systematic approach in the treatment of dry eye syndrome.